PENERAPAN SANKSI PIDANA DENDA TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOTIKA DI PENGADILAN NEGERI PADANG - Busnarma, Tommy (Soumatera Law Review, 2019)
The spirit and purpose of the Narcotics Law has not exceeded the expectations of its implementation. Every year the number of criminal narcotics continues to increase and does not seem to decline. One of the reasons is related to the application of very high fines while imprisonment due to fines are applied very briefly. The approach method used in this study is an empirical juridical method. This type of research is descriptive using primary data and secondary data. The results of the study indicate that judges' consideration in applying criminal penalties to narcotics defendants is based on juridical considerations and judicial non-judicial considerations. Judges are more likely to impose high prison sentences than to impose imprisonment in lieu of high fines, so that convicts do not assume that the economic level and wealth influence the criminal conduct they carry out. The judge does not have such a meaningful effort in the effort to apply criminal penalties to the narcotics defendant, the reason for the judge in applying a law must be based on existing legal rules. The judge applies the precautionary principle so that the judge does not enforce the law in a way that is against the law. The Prosecutor's Office has attempted to be able to implement criminal sanctions such as the issuance of SEJA, but prosecutors themselves are still experiencing difficulties in applying criminal penalties, both in terms of technical implementation and legal rules.